Post-Depletion Aggression Restrained: Replicability of Brief Mindfulness Induction In Indonesian Sample - Cleoputri Yusainy; Wahyu Wicaksono (Faculty of Psychology, Universitas Gadjah Mada, 2019)
Mindfulness practice is being promoted in Western countries as a means to improve one’s ability to restrain aggression under the “depleted” condition. The applicability of this framework in non-Western settings is yet to be determined. This study (N = 119 Indonesian undergraduates) directly replicated Yusainy and Lawrence (2015) experiment with native British sample, to examine the moderation of mindfulness induction on post-depletion aggression (i.e., blast intensity in an adapted competitive reaction-time task). Similar results were obtained, in that mindfulness induction moderated the ego-depletion and (i) blast intensity link under low/moderate provocation, and (ii) self-control performance link after the aggression task. Notably, the benefit of mindfulness was also indicated in our additional aggression measure of the late deliverance of maximum blast in depleted females. While Western operationalization of mindfulness operates quite similar across cultures, the inclusion of a subtle measure of aggression appears to be crucial for Indonesian females.